Publisher Correction: Ancient hybridization and strong adaptation to viruses across African vervet monkey populations. (November 2018) - Svardal, Hannes; Jasinska, Anna; Apetrei, Cristian; Coppola, Giovanni; Huang, Yu; Schmitt, Christopher; Jacquelin, Beatrice; Ramensky, Vasily; Müller-Trutwin, Michaela; Antonio, Martin; Weinstock, George; Grobler, J; et al.
In the version of this article published, in the Online Methods eight citations to supplementary material refer to the wrong supplementary items. See the correction notice for full details.